Działania w zakresie wybranych metod zarządzania w zakładach opieki zdrowotnej - Burda-Świerz, Katarzyna; Holecki, Tomasz (The tendencies for selected methods of management in health service administration, 2005)
Nowadays we can observe dynamic changes in health protection system. The management in health service administration in the present situation when there are plenty of needs not only requires proper techniques but also continuous improvements in management style. Under these circumstances the change is a condition of success. Polish health system, which is constantly rebuilding, requires professional and flexible leaders. This article is an attempt to present new methods of management in Polish health service administration.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 128-134